PARENTAL INVOLVEMENT AND ADOLESCENT AGGRESSION: EXPLORING THE LINK BETWEEN FAMILY ATTENTION AND BULLYING IN SCHOOLS - Yunila Sari; Wira Solina; Rila Rahma Mulyani (EDUCATIONE, 2026)
Bullying remains a recurring issue in school settings and may be influenced by the quality of parental attention. This study aimed to (1) describe parental attention among seventh-grade students, (2) describe students’ bullying behavior, and (3) examine the relationship between parental attention and bullying behavior at SMP Negeri 2 Lubuk Sikaping. A quantitative correlational design was employed. The population and sample comprised 52 seventh-grade students selected through total sampling. Data were collected using self-report questionnaires measuring parental attention (36 items) and bullying behavior (35 items). Descriptive statistics (percentages) and Pearson product–moment correlation were used for data analysis. Findings indicated that parental attention was predominantly high (100%), while bullying behavior was generally low (65% low; 31% very low; 4% moderate). Correlation analysis revealed a significant negative association between parental attention and bullying behavior (r = −0.307, p = 0.027), indicating that higher parental attention was linked to lower bullying tendencies, although the magnitude of the relationship was small. The study concludes that parental attention functions as a protective factor against bullying among students in this context. Practically, the findings support strengthening parent–school collaboration, including parenting guidance, routine supervision, and school-based reporting and counseling mechanisms to prevent bullying. Future research should use larger and more diverse samples, apply longitudinal approaches, and examine potential mediators (e.g., peer norms, school climate, and family communication patterns).